EXPLORING TEACHER CANDIDATES’ ASSESSMENT LITERACY: IMPLICATIONS FOR TEACHER EDUCATION REFORM AND PROFESSIONAL DEVELOPMENT - Volante, Louis; Fazio, Xavier (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
This study examined the assessment literacy of primary/junior teacher candidates in all four years of their concurrent program. Candidates from each year of the program completed a survey pertaining to self‐described level of assessment literacy, main purposes of assessment, utilization of different assessment methods, need for further training, and suggested methods for promoting assessment literacy in university and practice teaching settings. Levels of self‐efficacy remained relatively low for teacher candidates across each of the four years of this program. Most candidates suggested summative purposes for assessment and only a minority expressed formative purposes. They favoured observational techniques and personal communication. Key words: classroom assessment; preservice education Cette étude porte sur la capacité d’évaluation chez les étudiants en pédagogie durant les quatre années de leur programme de formation à l’enseignement au primaire et au premier cycle du secondaire. Des étudiants de chaque année du programme ont rempli un questionnaire portant sur les sujets suivants : auto‐estimation de leur aptitude à l’évaluation, buts principaux des évaluations, utilisation de diverses méthodes d’évaluation, besoin d’une formation plus poussée et suggestion de méthodes pouvant aider à perfectionner l’aptitude à l’évaluation à l’université et lors de stages pédagogiques. Les répondants dans chacune des années du programme estimaient que leur capacité d’évaluation était relativement faible. La plupart ont parlé d’évaluations sommatives et seulement une minorité, d’évaluations formatives. Les répondants favorisaient les techniques d’observation et les communications personnelles. Mots clés : évaluation des élèves, formation à l’enseignement